2017
DOI: 10.1186/s40104-017-0183-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of three lactobacilli with strain-specific activities on the growth performance, faecal microbiota and ileum mucosa proteomics of piglets

Abstract: BackgroundThe beneficial effects of Lactobacillus probiotics in animal production are often strain-related. Different strains from the same species may exert different weight-gain effect on hosts in vivo. Most lactobacilli are selected based on their in vitro activities, and their metabolism and regulation on the intestine based on strain-related characters are largely unexplored. The objective of the present study was to study the in vivo effects of the three lactobacilli on growth performance and to compare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 43 publications
2
18
0
Order By: Relevance
“…These findings are supported by earlier studies that showed positive effects on feed intake and growth performance in piglets fed diets supplemented with a complex of lactic acid bacteria during a 21-day post-weaning period [18]. The enhanced growth performance observed in our study is consistent with previous published reports [9,19,20].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These findings are supported by earlier studies that showed positive effects on feed intake and growth performance in piglets fed diets supplemented with a complex of lactic acid bacteria during a 21-day post-weaning period [18]. The enhanced growth performance observed in our study is consistent with previous published reports [9,19,20].…”
Section: Discussionsupporting
confidence: 93%
“…The EBL with Lactobacillus paracasei L9 had a more favorable effect on fecal microbial communities than the use of EBS, and the day21_EBL treatment was clustered into different groups from the control treatment. This result is in the line with the findings that Lactobacilli significantly modify intestinal microbiota in piglets, and reduce the PWD of piglets [9].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…L. reuteri is able to influence the diversity, composition and metabolic function of the gut, oral, and vaginal microbiotas. These effects are largely strain-specific ( Yang Y. et al, 2015 ; Garcia Rodenas et al, 2016 ; Galley et al, 2017 ; Su et al, 2017 ).…”
Section: Probiotic Properties Of L Reuterimentioning
confidence: 99%
“…The presence of probiotic strains of other Lactobacillus species was evaluated by DGGE in faecal samples (15,18), in the sour dough (19) as well as in naturally fermented lactic acid products (20). Using DGGE three lactobacilli were found able to modify intestinal microbiota in piglets (21). In the present study, the presence of selected L. bulgaricus strain in intestinal samples of volunteers consumed yoghurt containing this strain was assessed for the first time.…”
Section: Resultsmentioning
confidence: 94%